2020
DOI: 10.5194/hess-2020-597
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of automated flood inundation mapping methods in a context of flash floods: a comparison of three methods based either on the Height Above Nearest Drainage (HAND) concept, or on 1D/2D shallow water equations

Abstract: Abstract. Flash floods observed in headwater catchments often cause catastrophic material and human damage worldwide. Considering the large number of small watercourses possibly affected, the use of automated methods for flood inundation mapping at a regional scale can be of great help for the identification of threatened areas and the prediction of potential impacts of these floods. An application of three mapping methods of increasing level of complexity (HAND/MS, caRtino 1D, and Floodos 2D) is presented her… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…This implies that the minimum n SRC flood maps had more significant over-estimations of flood extents than under-estimations. This is most likely a result of the HAND model itself, as it can result in overestimations in flatter geographical regions (Hocini et al 2020) and the Riviere Richelieu site does have a low-moderate river gradient (0.0013 m/m) and flat terrain slopes. Further, it was noticed in the minimum n SRC flood maps (Figs.…”
Section: Comparison Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that the minimum n SRC flood maps had more significant over-estimations of flood extents than under-estimations. This is most likely a result of the HAND model itself, as it can result in overestimations in flatter geographical regions (Hocini et al 2020) and the Riviere Richelieu site does have a low-moderate river gradient (0.0013 m/m) and flat terrain slopes. Further, it was noticed in the minimum n SRC flood maps (Figs.…”
Section: Comparison Resultsmentioning
confidence: 99%
“…Flat terrains are also a challenge for the HAND model, as the model tends to over-estimate flood extents in these locations; this is a limitation shared with CERC-HAND-D, as the HAND model is required for creating SRCs. Further, the HAND model has been shown to be outperformed by Hydraulic 1D and 2D SWE models, albeit with higher computation times, and the model cannot produce outputs such as velocity and shear stress, which are important for flood hazard assessments (Hocini et al 2020;Rebolho et al 2018). Despite this, results such as those found by McGrath et al (2018) suggest that the HAND model can be a cost-effective, rapid, and accurate flood model that would be suitable for on-the-fly flood mapping.…”
Section: Discussionmentioning
confidence: 99%
“…The metric is also sensitive to the shoreline length to inundated area ratio (Stephens et al, 2014) so that what constitutes a 'good' match varies between sites. CSI values are therefore invariably less than 1 and this results from both model uncertainties (Hocini et al, 2020) and errors in observed data (Hawker et al, 2020;Horritt et al, 2001), both of which can be significant. To put the CSI scores achieved in this paper in context, comparison of modelled flood inundation extent with observations from airborne or satellite sources for individual river reaches typically results in CSI values in the range 0.65-0.9 (Aronica et al, 2002;Horritt & Bates, 2001a, with the higher value only ever achieved for sites with very high quality input and validation data Neal et al, 2009).…”
Section: Model Validationmentioning
confidence: 99%
“…(2018) developed a methodology for determining stage‐discharge relationships known as SRCs by sampling reach‐averaged parameters from HAND data sets and inputting into the Manning's equation (Gauckler, 1867; Manning et al., 1890). This collection of methods, coupling HAND with SRCs, have been experimented with and compared to other sources of FIM including engineering scale models, in‐situ observation, and remote sensing based observation with solid results in large spatial scale applications (Afshari et al., 2018; Godbout et al., 2019; Garousi‐Nejad et al., 2019; Hocini et al., 2020; Johnson et al., 2019; Nobre et al., 2016; Teng et al., 2015, 2017; J. Zhang et al., 2018; Zheng, Maidment, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…HAND, to our knowledge, has only been applied to natural, inland, and riverine inundation applications thus it is also missing pluvial, coastal, ground water, and dam break components among other possible sources of flooding. Additionally, in order to flood an area, HAND assumes all areas eligible for inundation must drain to some nearest flowpath which is used for catchment allocation and relative elevation calculation (Garousi‐Nejad et al., 2019; Hocini et al., 2020; Johnson et al., 2019; Y. Y. Liu et al., 2016; Y. Liu et al., 2020; Maidment, 2017; Nobre et al., 2011, 2016; Rennó et al., 2008; Zheng, Maidment, et al., 2018; Zheng, Tarboton, et al., 2018). Stream thalweg networks must also collectively drain to a singular outlet point for a given processing region (Nobre et al., 2016; Rennó et al., 2008; Zheng, Maidment, et al., 2018).…”
Section: Introductionmentioning
confidence: 99%